Žižek, Slavoj. (2005). Bienvenidos al desierto de lo real. Madrid: Akal. ISBN-13: 978-84-460-2038-7. 125. Número de páginas: 125. - Gamba Amaya, Francisco; Pontificia Universidad Javeriana (2015)
null